The effect of social connections on capital structure in supplier-customer relationships - Jandik, Tomas; Salikhova, Tatiana (Journal of Corporate Finance, 2023)
Suppliers socially connected to major customers with relation-specific investments have higher leverage ratios compared to unconnected suppliers. The presence of connections partially reduces supplier underleverage observed in supplier-customer relationships with relation-specific investments. Consistent with the role of connections in bonding trading parties' commitment, connections to major customers help to increase customer purchases, and supplier leverage increases are primarily observed in firms with high intensity of customer purchases. Additionally, connected suppliers are associated with higher leverage primarily when information asymmetry between parties is high. Overall, connections help strengthening implicit contracts through establishing trust between trading parties.